Cloning, Expression, Invasion, and Immunological Reactivity of a Mammalian Cell Entry Protein Encoded by the mce1 Operon of Nocardia farcinica - Ji, Xingzhao; Tan, Xiaoluo; Hou, Xuexin; Si, Chenchen; Xu, Shuai; Tang, Lu; Yuan, Xiuqin; Li, Zhenjun (Frontiers in Microbiology, 2017)
Bacterial mammalian cell entry (Mce) proteins have been implicated in pathogen invasion of mammalian host cells. The aim of this study was to examine the invasion-conferring ability of mce1E operon-encoded proteins, in vivo expression of Mce1E in cells from infected mice and rabbits, and Mce1E immunogenicity. Nocardia farcinica mce1E was cloned into pet30a(+) vectors, expressed in Escherichia coli, and purified. Invasion assays, transmission electron microscopy (TEM), immunoblots, and enzyme-linked immunosorbent assay (ELISA) detection of cytokines were conducted.TEM confirmed the invasion of HeLa cells by Mce1E-coated beads. The antigenicity of E. coli-expressed recombinant Mce1E was confirmed in immunoblots with sera from N. farcinica-infected mouse and rabbit sera. Co-incubation of Mce1E with splenocytes of N. farcinica-infected mice demonstrated upregulation of interferon (IFN-γ), but not interleukin (IL)-4 or IL-10, in the cultural supernatant. These findings demonstrate that Mce1E may facilitate N. farcinica interactions with and invasion of mammalian cells.Notably, Mce1E are expressed and elicited antibody responses in mice and rabbits during infection.Besides, it may play a role in cell-mediated immune reactions and cause host inflammation responses to N. farcinica infection.